Input parameters authentication through dynamic software watermarking - Pérez Gort, Maikel Lázaro (Frontiers in Computer Science, 2025)
Modern civilization relies on computers and the Internet. Web services and microservices make many processes more accessible, often without users realizing the extent of their dependency. As digitalization spreads, the integrity of input parameters used by programmed methods becomes crucial for generating accurate and reliable outcomes, which are essential for the proper functioning of society. This paper introduces a dynamic software watermarking approach designed to validate the authenticity of input parameters in high-level programming language functions. The proposed approach operates without interfering with software functionalities and is resilient to code optimization, obfuscation, and other transformations. The experimental results demonstrate the robustness of our method, ensuring 100% accuracy in detecting tampering with parameter values across all test cases.